Business Plan - AlSarah, Jamila (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: The purpose of this study is to present a complete business plan for the launch of" Saman Al Dar," a special product leveled at offering customers an authentic taste of Emirati cuisine. The plan encompasses numerous aspects, involving team structure, legit compliance, marketing strategies, fiscal protrusions, and ethical considerations. Methodology: The methodology involved in casting this business plan comprehended thorough request exploration to understand consumer preferences and request trends in the UAE food assiduity. The plan also incorporates rudiments of request blend proposition, Porter's competitive strategies, and SWOT analysis to develop a robust program for success. Also, a detailed analysis of cost, profit aqueducts, and return generation was conducted to insure fiscal viability. Findings: The finding of this study disclose a clear roadmap for founding Saman Al Dar successfully. Fiscal protrusions indicate encouraging profit generation implicit, especially with operative marketing and division strategies in position. Key findings carry the identification of target customer seeking authentic Emirati flavors, the significance of strategic marketing across different channels involving social media, and the significance of legit compliance and ethical practices in the food assiduity. Unique Contribution to Theory, Practice and Policy: This business plan contributes to proposition, practice, and procedure in several ways. The operation of request blend proposition, Porter's competitive strategies, and SWOT Analysis demonstrates their applicability and connection in the environment of entrepreneurial gambles in the food assiduity. Scholars of entrepreneurship can work these rulings to enrich their understanding of business planning and program perpetration. Likewise, policymakers can exercise the rulings to inform the evolution of a legit environment that fosters entrepreneurship, especially in the hospitality region, by ensuring regulatory frameworks that support invention and compliance while securing consumer interests. Also, entrepreneurs can profit from the perceptivity provided in this study, as the ideas and strategies offered are directly workable to their own business trials. In conclusion, this business plan for Saman Al Dar represents a holistic path to founding a special product in the UAE food request. By incorporating rigid exploration, strategic planning, and ethical considerations, it lays the foundation for a prosperous entrepreneurial adventure that not only delivers value to customers but also contributes to the wider academic and policy discourse surrounding entrepreneurship in the hospitality region.